Phenotypic and Genotypic Profiles of Extended-Spectrum Beta-Lactamase-Producing Multidrug-Resistant Klebsiella pneumoniae in Northeastern Thailand - Sumontha Chaisaeng; Nattamol Phetburom; Pachara Kasemsiri; Nuntiput Putthanachote; Naowarut Wangnadee; Parichart Boueroy; Anusak Kerdsin; Peechanika Chopjitt (MDPI AG, 2024)
The global emergence of extended-spectrum beta-lactamase (ESBL)-producing Klebsiella pneumoniae presents a significant public health threat and complicates antibiotic treatment for infections. This study aimed to determine the prevalence of ESBL-producing K. pneumoniae in a clinical setting, analyze their antimicrobial susceptibility profiles, and characterize both phenotypic and genetic determinants. A total of 507 non-duplicate clinical isolates of Enterobacterales were collected between 2019 and 2020, and third-generation cephalosporin resistance was screened by disk diffusion. Identification of K. pneumoniae was confirmed using biochemical tests and PCR with species-specific primers. Antimicrobial susceptibility testing was conducted using disk diffusion, and phenotypic ESBL production was confirmed using the combined disk method. Multiplex PCR detected ESBL genes (blaTEM, blaSHV, and blaCTX-M) and identified blaCTX-M groups. The genetic relatedness of ESBL-producing strains was assessed using the ERIC-PCR approach. Fitty-four isolates were confirmed as ESBL producers, all classified as multidrug-resistant (MDR). All ESBL-producing K. pneumoniae isolates exhibited resistance to ampicillin and cefotaxime, with high resistance rates for ciprofloxacin (98.2%), azithromycin (94.4%), piperacillin-tazobactam (88.9%), and trimethoprim (83.3%). Genotypic analysis revealed blaCTX-M was present in 94.4% of isolates, blaSHV in 87%, and blaTEM in 55.5%. The blaCTX-M-1 group was the most prevalent, accounting for 96.1% of isolates. Co-harboring of blaCTX-M, blaSHV, and blaTEM occurred in 42.6% of isolates, with co-carrying of blaCTX-M, and blaSHV was observed in 23/54 isolates. The ERIC-PCR analysis revealed 15 distinct types, indicating high genetic diversity. These findings highlight the urgent need for ongoing monitoring to control the spread of ESBL among K. pneumoniae and emphasize the importance of early detection and appropriate antibiotic selection for effectively treating infection caused by these pathogens.